2013
DOI: 10.1126/scitranslmed.3005066
|View full text |Cite
|
Sign up to set email alerts
|

Coronary Microvascular Pericytes Are the Cellular Target of Sunitinib Malate–Induced Cardiotoxicity

Abstract: Sunitinib malate is a multi-targeted receptor tyrosine kinase inhibitor used in the treatment of human malignancies. A substantial number of sunitinib-treated patients develop cardiac dysfunction, but the mechanism of sunitinib-induced cardiotoxicity is poorly understood. We show that mice treated with sunitinib develop cardiac and coronary microvascular dysfunction and exhibit an impaired cardiac response to stress. The physiological changes caused by treatment with sunitinib are accompanied by a substantial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
164
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 182 publications
(175 citation statements)
references
References 46 publications
9
164
0
2
Order By: Relevance
“…Elevations of blood pressure that might contribute to cardiac dysfunction were not detected following dosing of sunitinib and its analogues, verifying previously published reports (22). However, we did observe a reduction in the percentage of FS in mice treated with the various molecules.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Elevations of blood pressure that might contribute to cardiac dysfunction were not detected following dosing of sunitinib and its analogues, verifying previously published reports (22). However, we did observe a reduction in the percentage of FS in mice treated with the various molecules.…”
Section: Discussionsupporting
confidence: 92%
“…Clinical trials of sunitinib in tumors, such as prostate (18) and breast cancer (19) were initiated on the basis of successful preclinical evidence (16,20) but were halted in phase III, despite prolongation of progression-free survival, due to the lack of statistically significant overall survival in patients. Experience with sunitinib in the clinic demonstrated that a considerable subset of sunitinib-treated patients develop left ventricular (LV) dysfunction and overt heart failure (21,22).…”
Section: Introductionmentioning
confidence: 99%
“…Pericytes in the neurovascular niche have proven to be essential in diverse processes such as angiogenesis, vessel maturation, homeostasis and permeability, and vascular tone (Aguilera and Brekken, 2014;Armulik et al, 2011). Cardiotoxicity in sunitinib-treated patients has recently been attributed to the depletion of coronary pericytes and subsequent microvascular dysfunction (Chintalgattu et al, 2013), suggesting an equally important role for pericytes in the heart. However, there remains a significant lag in the understanding of coronary pericyte biology, which is partially due to the difficulty in unambiguously identifying and isolating pericytes in the heart.…”
Section: Discussionmentioning
confidence: 99%
“…As HIF-1 levels are diminished upon tyrosine kinase inhibition, it is rational to assume that TKI-associated cardiotoxicity become more prominent (7,8). In addition, loss of pericytes around microvessels in sunitinib-treated hearts has been demonstrated in vascular beds that lead to pericardial fluid accumulation via increased vascular permeability (9). Sunitinib also inhibits multiple receptor tyrosine kinases including platelet derived growth factor B (PDGFR B) which has a special function in angiogenesis and maintenance of tissue interstitial fluid pressure.…”
Section: Discussionmentioning
confidence: 99%